The Use of CUSB Model to Simplify Business Plans the Case of the Promotion of A Heritage Site in Morocco - Jorio Houda (Iraqi Journal of Science, 2021)
In today‟s fierce competitive world, entrepreneurship has taken an upswing because business owners are facing a technological challenge in which uniqueness and particularity are key elements to detour rivals. In this essence, entrepreneurs have to go by not only developing business plans but also a deep analysis of their environment.Business plans for entrepreneurs can take different models depending on the party that will evaluate its elements based on its requirements. However, there exists a basic format that most entrepreneurs follow. Because of time constraints, business owners are urging its usefulness and so are the investors. Business plans are all about nailing down the business idea into writing and analysis, while this seems a feasible task; there are plenty of external and internal research to be set set in order to accomplish it. Within these measures in place, there exists a quick yet effective model that could carry on the thought and set the startup business into action.The model is called business plan canvas; it is based on the CUSB model that serve both the business owner and or the investor to better catch on the business idea and understand its objectives and requirements starting by the customer, the non satisfied need, the solution, and the benefits to be offered. It is also a model that helps the potential entrepreneur to sell his thoughts in order to get some funds, counseling, and a road map to follow for his future business endeavor.